Social Engagement Meningkatkan Life Satisfaction Pasien Stroke - Nur Anisa, Mufida; Kurniawan, Hendri (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Post-stroke problems will affect daily activities, social engagement, and life satisfaction. Decreased life satisfaction is often associated with social engagement, which in turn affects the post-stroke recovery process. Objectives: The study aims to determine the influence of social engagement on the life satisfaction of stroke patients. Methods: The study used a quantitative method, a non-experimental type with a cross-sectional design. The selection of research subjects used a purposive sampling technique with a total of 45 research subjects. The research instruments used included: Social Disengagement Index and the Satisfaction with Life Scale. Analysis of research data used correlation and regression tests using the SPSS version 25. Results: The majority of research subjects demonstrate good social engagement at 73.3% and are categorized as satisfied with a life satisfaction rate of 82.2%. Research subjects with good social engagement tend to experience high levels of life satisfaction. The correlation test yielded a value of r = 0.771 and a p-value of 0.000, indicating a significant positive relationship between social engagement and life satisfaction. The regression test results showed a coefficient of determination (R-square) of 0.594, meaning that social engagement significantly influences life satisfaction by 59.4%, represented by the equation Y = 1.221 + 0.005X. Conclusion: Social engagement has a very strong positive correlation with the level of life satisfaction. Social engagement influences the increase in life satisfaction of stroke patients by 59.4%. Keywords : stroke, social engagement, life satisfaction